State-of-the-art review of nanofluids in solar collectors: A review based on the type of the dispersed nanoparticles. (10th August 2021) - Xiong, Qingang; Hajjar, Ahmad; Alshuraiaan, Bader; Izadi, Mohsen; Altnji, Sam; Shehzad, Sabir Ali
Abstract: Nanofluids as a new generation of fluids have attracted a lot of research works. There is growing evidence that the nanofluids are more suitable for various heat transfer applications than the conventional fluids. One of the most important parameters in the thermal behavior of such fluids is the type of nanoparticles dispersed in the base fluid. The present review paper is devoted to provide an overview on the distinct types of particles used in nanofluid research with emphasis on their application in solar collectors. The impact of nanofluids on heat transfer under different dispersive particles is explained for both numerical and experimental researches. Works concerning the application of nanofluids in solar collectors are singled out and analyzed. The nanoparticles are classified into metallic and non-metallic and the various configurations of solar collectors are considered. The review indicates that the flat plate solar collectors are the most investigated among the considered configurations. It is also shown that Al2 O3 -based nanofluids have been widely considered in these collectors compared to other nanofluids. In addition, the non-metallic based nanofluids can be more useful for the efficiency enhancement of solar collectors compared to metal based nanofluids. Some negative aspects related to nanofluids are also pointed out such as the thermo-physical instability and the reduced efficiency at high nanoparticle volume fraction. Finally, the general conclusions are drawn and future directions for research are proposed. It is noted that the present review concerns the nanofluids based on a single nanoparticle type. Hybrid nanofluids are subject to a future review. Graphical abstract: Image 1 Highlights: Flat plate solar collectors are the most investigated among other configurations. Al2 O3 -based nanofluids have been widely considered in solar collectors. The results of Newtonian and non-Newtonian nanofluids are compared and discussed. Non-metallic based nanofluids can be more useful for the efficiency of SC.